The De-Sexualization of the Harem: How Europe's Female Artists Resisted and Embraced the Male Gaze on the Harem - Tranter, Nuala (Culture and History: Student Research Papers, 2025)
In a discourse consumed by the paintings and writings produced by the male gaze, female reproductions of the Orient remain a largely undiscovered facet of colonial history and discourse. Female contributions to the European image of the Oriental are evidence of their active role in imperial power relations, establishing her firmly in an intersection between race, gender, and colonialism. Thus, as this article traces the female gaze on the harem, the inclusion of women in the masculine phenomenon of imperialism and colonialism will also be revealed. By analysing paintings produced from 1850 to 1900, the female creator becomes a focal point in Oriental history.